Property-Tax Reform: The Land-Value Tax as a Practical Alternative? - Thiess Büttner; Horst Zimmermann (Wirtschaftsdienst)
Abstract Germany is currently reforming its municipal property tax. To simplify the assessment, some German states are considering a land-value tax as a practical alternative. The authors discuss the pros and cons and find some merit in the land-value tax. However, they suggest that states implement precursions to prevent excessive taxation, such as setting a maximum tax rate.